2022
DOI: 10.20944/preprints202201.0140.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal and Spatial Evolution of Climate Comfort and Population Exposure in Guangdong Province in the Last Half Century

Abstract: Regional Climatic Comfort Index (CCI) deteriorated significantly due to the climate change and anthropogenic interference. Knowledge regarding the long-term temporal dynamics of CCI in typical regions should be strengthened. In this study, we analyze the temporal and spatial evolution of CCI from 1969 to 2018 in Guangdong Province, based on meteorological indicators, including heat, humidity, wind and cloth loading etc.. Additionally, the population exposure to climate unconformity was examined since 1990 with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Aphyocypris normalis Nichols and Pope, 1927 is a freshwater fish that ranges over southern mainland China and Hainan Island [ 18 ], as well as Vietnam on the Indochina Peninsula [ 19 ]. In mainland China and Hainan, we have observed that A .…”
Section: Introductionmentioning
confidence: 99%
“…Aphyocypris normalis Nichols and Pope, 1927 is a freshwater fish that ranges over southern mainland China and Hainan Island [ 18 ], as well as Vietnam on the Indochina Peninsula [ 19 ]. In mainland China and Hainan, we have observed that A .…”
Section: Introductionmentioning
confidence: 99%